Hubungan Antara Layanan Keperawatan Dengan Tingkat Kepuasan Pasien Di Klinik Pratama Badan Pusat Statistik : The Relationship Between Nurse Services and Patient Satisfaction Levels at the Pratama Clinic of the Central Bureau of Statistics - Wijayanti, Ruri (Dohara POAJ, 2025)
Introduction: Nurse services is said to be good if the fulfillment of patient needs goes according to standards and good service will create a level of patient satisfaction according to standard. There are 5 factors that influence patient satisfaction namely responsiveness, reliability, assurance, empathy and tangibles. With these factor patients can assess how the nursing services they receive and can perceive whether they are in accordance with what the patient wants or not. Methods: The data scale of this study is ordinal scale and uses the Spearman statistical test. The Spearman Rho is one of the non-parametric associative bivariate tests. This mean that the non-parametric test is used to see the strength of a relationship between two variables that have an ordinal measurement scale. Results: The results of the research showed that the results of the Spearman statistical test for the variable Nurse Services and Satisfaction had a degree of significance p (0,001); which means that the results of the statistical test showed p < 0,05; so H1 was accepted and it meant that there was a relationship between the two variables. Judging from the results of the Correlation Coefficient or how strong a relationship between the two variables is the result is 0,744 which means very strong. Discussion: There is a relationship between nurse services and the level of patient satisfaction at the Primary Clinic of the Central Bureau of Statistics.